Assessment of the biophysical conditions of caves promoted for ecotourism in Mabinay, Negros Oriental, Philippines - Alcala, Ely; Averia, Leonardo; Tababa, Luis; Dagunan, Mary Ann; Tababa, Reynaldo; Dasian, Jeffrey; Libo-on, Elery Vaughn; Ocampo, Michael (2007)
Five caves promoted for ecotourism in Mabinay, Negros Oriental were studied by a team composed of researchers, cave guides, and professional cavers to determine their viability for tourism and impact of caving activities. Several criteria were used including assessment of threats to bats and bat cave inhabitants. Cave assessment was supplemented with interviews of local residents. Results of the study indicated that all five caves were utilized by bats as roosting sites but were disturbed by hunting and caving activities. At least 11 species of bats were found in the study area. Of the five caves, three adjoining caves were identified as ideal caving destinations for moderate cavers. One cave is recommended for extreme caving activities, and another one for special cave destination (bat cave habitat viewing). Recommendations to improve the current cave tourism are provided.
Keywords: Caves -- Mabinay (Negros Oriental)